2019
DOI: 10.3390/su11174642
|View full text |Cite
|
Sign up to set email alerts
|

Constructivism-Based Methodology for Teaching Artificial Intelligence Topics Focused on Sustainable Development

Abstract: This article proposes the creation of a course based on a series of practical sessions, where the students have to develop their practical knowledge about artificial intelligence techniques, specifically multilayer perceptron. The novelty of this paper is based on the constructivism methodology regarding artificial intelligence and sustainable development. Moreover, it can be implemented in different majors because of the flexibility in certain aspects. It is oriented to evaluate skills in the broad education … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Across the literature, there are other subtle methodologies for teaching programming and related courses, including the constructivist‐based approach [95], Short‐Term Fourier (STFT) and Continuous Wavelet Transform (CWT) [101], fuzzy logic [144], game‐based learning, and collaborative programming [19]. Similar to program animations, these methodologies have also reported promising results.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Across the literature, there are other subtle methodologies for teaching programming and related courses, including the constructivist‐based approach [95], Short‐Term Fourier (STFT) and Continuous Wavelet Transform (CWT) [101], fuzzy logic [144], game‐based learning, and collaborative programming [19]. Similar to program animations, these methodologies have also reported promising results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar to program animations, these methodologies have also reported promising results. For example, Mota‐Valtierra et al [95] proposed a constructivist‐based approach to teach artificial intelligence topics and found an increase in the growth progression of students' grades across 4years period. A recent review that compared different programming methods demonstrated that program animation and game‐based learning enhance students' computational thinking and problem‐solving skills [19].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial intelligence Constructivism-based methodology for teaching artificial intelligence topics focused on sustainable development [14]. tools in addition to R language, which is helpful in the development of a project.…”
Section: Mechatronicsmentioning
confidence: 99%
“…In , a new teaching method for the AI course is proposed. The course first teaches students theoretical knowledge and then introduces students to practice.…”
Section: Introductionmentioning
confidence: 99%